Students' Mathematical Connection Skills Reviewed From Learning Styles - Ujang Suprianto; Heni Pujiastuti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2020)
The purpose of this study is to determine the distribution of student learning styles, to determine the average mathematical communication skills that have Auditory, Visual, and Kinestatic learning styles. and to find out if there are significant differences in the ability of mathematical connections between students who have auditory, visual, and kinesthetic learning styles. This research was conducted at SMAN 17 Pandeglang in class XII MIPA. The instrument used was in the form of a learning style questionnaire and a test of mathematical connection abilities. This type of research is a comparative study with a quantitative approach. Based on the results of data processing, that the distribution of student learning styles is included in the Auditory learning style of 34% of students, Visual 46% of students, and Kinesthetic 19% of students. By using a scale of 0-50, the average mathematical connection ability of students is 29.58, whereas when viewed from each distribution of learning styles, the average mathematical ability of auditory students is 24.89, visual students 28.33, and kinestatic students 34,40. Based on the results of the analysis with the ANOVA test and t test (Dunnet) that there is a significant difference in the ability of students' mathematical connections between auditory, visual and kinesthetic learning styles with a significant level of ? = 0.05, and the results of the value of Fcount > Ftable = 3.62 > 3,42, where the kinesthetic learning style has higher mathematical connection ability than auditory and visual learning styles.